Testing-as-a-Service Market Situation in Finland in Terms of Quality - Alarinta, Eveliina (My University, 2024)
This thesis explores the Testing-as-a-Service (TaaS) market in Finland, with a particular focus on service quality and adoption within the software testing landscape. As software development becomes increasingly complex, driven by the adoption of cloud services, the need for efficient software quality assurance (QA) has grown. TaaS, a cloud-based solution, offers organizations flexibility and scalability by outsourcing testing services on demand. The study aims to answer a research question: What is the current Testing-as-a-Service Market Situation in Finland in Terms of Quality? This research was conducted in collaboration with Fellowmind Finland Oy Ab, which offers, among other things, a broad range of services including ERP, data analytics, CRM, AI solutions, cloud security, IT infrastructure, project management, business planning, application development, and modern workplace solutions. The research is based on a survey, supplemented by two interviews with industry professionals. The survey provides a broad overview of TaaS adoption in Finland, focusing on aspects such as service quality, scope of testing, and current usage rates. The interviews offer deeper qualitative insights into the experiences of professionals who have used or considered using TaaS solutions, enriching the data from the survey. The thesis is structured as follows: Chapter 2 reviews literature on software testing and QA, including testing types, automation strategies, and tools, and discusses the role of TaaS in continuous software engineering. Chapter 3 outlines the methodology used, detailing the survey process and interviews. Chapter 4 presents and analyzes the results from the survey and interviews. Chapter 5 summarizes the conclusions and suggests areas for future research. Finally, all the appendices can be found at the end of the study. This research aims to explore the TaaS market in Finland while also contributing to the broader discussion on software testing practices. It provides practical insights for companies considering TaaS as part of their QA strategy, offering recommendations for enhancing software quality through cloud-based testing solutions. Tämä opinnäytetyö tutkii Testing-as-a-Service (TaaS) -markkinoita Suomessa keskittyen erityisesti palvelun laatuun ja käyttöönottoon ohjelmistotestausympäristössä. Ohjelmistokehitys muuttuu yhä monimutkaisemmaksi pilvipalvelujen käyttöönoton myötä, ja tarve tehokkaalle ohjelmiston laadunvarmistukselle (QA) on kasvanut. Pilvipohjainen TaaS tarjoaa organisaatioille joustavuutta ja skaalautuvuutta ulkoistamalla testauspalvelut tarpeen mukaan. Tutkimus pyrkii vastaamaan tutkimuskysymykseen: Mikä on "testaus palveluna" -markkinatilanne Suomessa tällä hetkellä? Tämä tutkimus tehtiin yhteistyössä Fellowmind Finland Oy Ab:n kanssa, joka tarjoaa mm. laajan valikoiman palveluita, kuten ERP, data-analytiikka, CRM, AI-ratkaisut, pilvitietoturva, IT-infrastruktuuri, projektinhallinta, liiketoimintasuunnittelu, sovelluskehitys, ja nykyaikaiset työpaikkaratkaisut. Tutkimus perustuu kyselyyn, jota on täydennetty kahdella alan ammattilaisen haastattelulla. Tutkimus tarjoaa laajan yleiskatsauksen TaaS:n käyttöönotosta Suomessa keskittyen muun muassa palvelun laatuun, testauksen laajuuteen ja nykyiseen käyttöasteeseen. Haastattelut tarjoavat syvempää laadullista näkemystä TaaS-ratkaisuja käyttäneiden tai sitä harkitsevien ammattilaisten kokemuksista, rikastaen samalla kyselyn tietoja. Opinnäytetyö on rakenteeltaan seuraava: Luvussa 2 tarkastellaan ohjelmistotestausta ja laadunvarmistusta koskevaa kirjallisuutta, mukaan lukien testaustyypit, automaatiostrategiat ja työkalut, sekä pohditaan TaaS:n roolia jatkuvassa ohjelmistosuunnittelussa. Luvussa 3 hahmotellaan käytetyt menetelmät sekä kyselyprosessi ja haastattelut. Luvussa 4 esitellään ja analysoidaan kyselyn ja haastattelujen tuloksia. Luvussa 5 esitetään yhteenveto päätelmistä ja ehdotetaan alueita tulevaa tutkimusta varten. Lopuksi kaikki liitteet löytyvät tutkimuksen lopusta. Tämän tutkimuksen tavoitteena on tutkia TaaS-markkinoita Suomessa ja samalla edistää laajempaa keskustelua ohjelmistojen testauskäytännöistä. Se tarjoaa käytännön näkemyksiä yrityksille, jotka harkitsevat TaaS:ää osana laadunvarmistusstrategiaansa. Se tarjoaa suosituksia ohjelmistojen laadun parantamiseen pilvipohjaisten testausratkaisujen avulla.
Keywords: testing; cloud services; quality control; computer programmes; automation; software engineering; quality; software technology; testing methods; information technology; fi=Tuotantotalous (kauppatieteet)|en=Industrial Management|; Master's Programme in Industrial Management